Analysis of the Utilization of Information and Communication Technology in the Communication and Information Services of Batu City in Supporting the Realization of Batu City as a “Smart City” - Adi, Tutri Laksono; Hidayatullah, Syarif; Respati, Harianto (International Journal of Scientific Research and Management (IJSRM), 2022)
With the use of information and communication technology brings ease of information for the community. Through an application system, various information about the city can be accessed quickly by the community and the local government through a program called Smart City. Smart City has been implemented in various cities in the world and has been proven to be able to solve various problems quickly as well. This information can also be used by local governments to create comfort, security and order and a better life. The purpose of writing this article is to obtain an overview of the use of information and communication technology at the Department of Communication and Information Technology of Batu City to realize Batu City as a Smart City. For that, it is necessary to do several things that support the use of information and communication technology so that it can realize Batu City as a smart city. However, of course there are several things that must be implemented so that the smart city program can run smoothly in Batu City.